Editorial: Comorbidities in Women With Endometriosis: Risks and Implications - Holdsworth-Carson, Sarah J.; Ng, Cecilia H. M.; Dior, Uri P. (Frontiers in Reproductive Health, 2022)
Women with endometriosis suffer lengthy diagnostic delay. In part, this is the consequence of nonspecific and overlapping symptomology with common gynaecological and other diseases. As such, endometriosis may be confused or misdiagnosed as an entirely different condition. The challenge for health professionals is increased further by growing observations indicating that people with endometriosis also demonstrate a high incidence of gynaecological and non-gynaecological comorbidities and chronic conditions. The aim of our Research Topic was to highlight existing evidence-based research, or lack thereof, that aligns comorbid and chronic conditions with endometriosis.